A PEGylated bovine hemoglobin as a potent hemoglobin‐based oxygen carrier. (31st October 2016) - Wang, Ying; Wang, Linli; Yu, Weili; Gao, Dawei; You, Guoxing; Li, Penglong; Zhang, Shan; Zhang, Jun; Hu, Tao; Zhao, Lian; Zhou, Hong
Abstract : Hemoglobin (Hb)‐based oxygen carriers (HBOCs) have been used as blood substitutes in surgery medicine and oxygen therapeutics for ischemic stroke. As a potent HBOC, the PEGylated Hb has received much attention for its oxygen delivery and plasma expanding ability. Two PEGylated Hbs, Euro‐Hb, and MP4 have been developed for clinical trials, using human adult hemoglobin (HbA) as the original substrate. However, HbA was obtained from outdated human blood and its quantity available from this source may not be sufficient for mass production of PEGylated HbA. In contrast, bovine Hb (bHb) has no quantity constraints for its ample resource. Thus, bHb is of potential to function as an alternative substrate to obtain a PEGylated bHb (bHb‐PEG). bHb‐PEG was prepared under the same reaction condition as HbA‐PEG, using maleimide chemistry. The structural, functional, solution and physiological properties of bHb‐PEG were determined and compared with those of HbA‐PEG. bHb‐PEG showed higher hydrodynamic volume, colloidal osmotic pressure, viscosity and P50 than HbA‐PEG. The high P50 of bHb can partially compensate the PEGylation‐induced perturbation in the R to T state transition of HbA. bHb‐PEG was non‐vasoactive and could efficiently recover the mean arterial pressure of mice suffering from hemorrhagic shock. Thus, bHb‐PEG is expected to function as a potent HBOC for its high oxygen delivery and strong plasma expanding ability. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 33:252–260, 2017